A apreensão do gênero projeto de pesquisa por alunos do curso de licenciatura em letras - Leitão, Poliana Dayse Vasconcelos (2008)
Low performance in reading activities and, mainly, in writing is a problem that affects students of all ages and levels of education, including higher education, in several subjects. Therefore, the expansion of literacy practice has been one of the main objectives of Education in recent years, particularly of professionals who work with language teaching. This expansion requires a new conception of teaching-learning of reading and writing, based on the study of textual genres, with emphasis on their social-historical-ideological aspects. It also requires that we teachers should have a critical-reflective positioning, in which we play the role of researcher and literacy agents. For this, we needed to grasp different textual genres, among them, the academic and scientific, and particularly the Research Project. Several theoretical and methodological proposals have emerged in order to help us to take these difficulties and these essential tasks. One of the most complete is the Social-discursive Interactionism (SDI), because it considers language as unit of analysis, the active conducts and the conscious thought in order to explain the process of texts-discourses production, considering it as a tool to human development. Our work is situated in this theoretical and methodological approach and aims at investigating the process of the textual genre Research Project for pre-graduate students in Literature. To achieve the objective mapped out, we conducted an action research with Modern Languages students of the sixth semester of a private institution of the state of Bahia. Our tools for data collection were direct observation and participatory implementation of a Pre-Test, of a Post-Test and several activities of production and rewriting. We organized the results of our research into four chapters: 1 Teacher development and Academic Literacy (HENGEMUHLE, 2007; TARDIF, 2002; AMARAL, and MOREIRA RIBEIRO, 1996; LOPES, 1997; SOARES, 1998 and 2005; Bazerman, 2006; OLSON , 1997; KLEIMAN, 1995 and 2006, and MATENCIO, 2006); 2 Social-discursive Interactionism: path to support the analysis and the scaling of literacy practices(BRONCKART, 1999 and 2006 and MACHASDO, 2005); 3 Research Project: the first step to the development of investigative attitude (ABNT NBR 15287: 2005; GIL, 2002; LUNA, 2006; MICHEL, 2005; Bagno, 1998; MACHADO, LOUSADA and ABREU-TARDELLI, 2005), and 4 The understanding of the Genre Research Project for Students of undergraduate Course in Literature: a process of (re) construction of knowledge. We concluded that initial representations relating to both the concept and the superstructure of the genre studied focuses predominantly on the textual typology discourse. Meanwhile, the final representations are guided into the version of the research project studied in the classroom. Items which have caused more difficulties were: the problems, because of the background knowledge triggered by vocabulary which named this item, usually related to the difficulty, and the objectives, by not differentiating the personal, the teaching and research objectives. Based on analyzed the data, it was found that the apprehension of the genre Research Project triggers a continuous process of (re) construction of knowledge, especially linguistic-textual and enunciative-discursive knowledge as well as the reconstruction of concepts concerning the genre itself.